422 A review of bone health in children and young people with limited motor function in South Wales. (17th August 2022) - McGrath, Nicole; Saunders, Joanne
Abstract : Aims: Bone health is an increasingly recognised problem in children and young people (CYP) with long-term conditions causing limited motor function. Reduced motor function is associated with low bone mineral density. In addition, CYP with complex needs are often exposed to risk factors for nutritional deficiencies. Long term reduced mobility is known to increase the risk of pathological fractures and osteoporosis, which can lead to progressive disability. Regular bone health monitoring is essential to maintain the highest possible level of function. NICE have recommendations for bone health monitoring for Duchenne's muscular dystrophy and cerebral palsy. This guidance has established risk factors which can be used to identify CYP at increased risk of pathological fractures, providing auditable recommendations for monitoring. Methods: We completed a retrospective audit of digital records, including clinic letters, diagnostic imaging and biochemistry testing. Children were identified using documented gross motor function classification scale (GMFCS) on physiotherapist caseloads. This included children from community and special school clinics. We identified clinical risk factors linked to increased fracture risk in children with underlying medical conditions (1). These include: Prolonged reduced mobility (GMFCS IV-V). Poor nutrition. We considered method of feeding and weight. Biochemical risk factors: Insufficient calcium and Vitamin D. Pharmacological risk factors: corticosteroids and anti-epileptic medication. Previous fractures: either pathological or traumatic. Results: 134 CYP were identified. This includes 57 with GMFCS V (41.6%), 77 (57.4%) with GMFCS IV. 64 children (47%) are seen in a specialist school setting. Aetiology for this cohort included 78 with cerebral palsy (50%), 24 (15.4%) with neurological conditions, 22 with genetic syndromes (14.1%), 8 with neuromuscular conditions (5%). Other diagnoses included ABI, Down syndrome, and spina bifida. Risk factors for pathological fractures were identified in 57 (42%) patients (figure 1), with multiple risk factors in 11 (9%). 11 children were found to have a history of fractures, of which 6 were pathological (54%). A full biochemical profile was available in 57 patients (42.5%), of which abnormalities were identified in 14 (10.4%), most commonly vitamin D deficiency (figure 2). Of note, only 5 CYP in this cohort were prescribed vitamin D supplements. Conclusion: This review shows there is scope for improvement in bone health monitoring for CYP with disabilities. There also needs to be consensus on target Vitamin D levels (as laboratory levels 'sufficient in most people' are probably insufficient for high-risk CYP). The cerebral palsy register for Wales will provide an excellent opportunity to improve health surveillance for this cohort of CYP. This could be used as a platform for routine monitoring of children with complex disabilities, which may reduce health disparities in high-risk patients. Recommendations for future practice: Review of bone health to be incorporated in annual review for CYP with complex needs, including assessment of risk factors. Routine biochemical monitoring of bone health, including vitamin D levels. Supplementation of calcium and vitamin D in children at risk of pathological fractures. Consideration of bone mineral density assessment if risk of pathological fractures.